Broadband spectro-temporal study on blazar TXS 1700+685. Issue 4 (23rd July 2022) - Banerjee, Anuvab; Nandi, Prantik; Prince, Raj; Khatoon, Rukaiya; Bose, Debanjan
ABSTRACT: We attempt to present a multiwavelength variability and correlation study as well as detailed multiwaveband spectral characteristics of the May 2021 gamma-ray flare of the blazar source TXS 1700+685. The multiwavelength observation from Fermi -LAT, Swift -XRT/UVOT as well as radio archival data are used for our spectro-temporal investigation. We estimate the variability time-scale of the source from the flux doubling time in different flaring region detected in Fermi -LAT observation and the shortest variability time is used to put a constraint on the minimum Doppler factor and on the size of the emission region. We have detected a statistically significant quasi-periodic oscillation feature at ∼17 d. The broad-band emission is satisfactorily represented during its flaring state with a leptonic synchrotron and inverse Compton component. From the broad-band spectral modelling, we observe the external Comptonization of the seed photons originating in the broad-line region to be dominant compared to the dusty torus. The equipartition value implies the energy density of the magnetic field in the jet comoving frame is weak. In order to produce the high-energy hump, we need the injection of a large population of high-energy electrons and/or the presence of strong magnetic field; and we observe the later component to be subdominant in our case. The gamma-ray spectral energy distribution shows the flat rising and steep falling profile, as well as the break or spectral curvature at ∼1 GeV, which has been seen for other flat-spectrum radio quasar sources before.